2019
DOI: 10.2147/copd.s189010
|View full text |Cite
|
Sign up to set email alerts
|

<p>Trends and hospital outcomes of lung transplantation among patients with and without chronic obstructive pulmonary disease in Spain: a national population-based study (2001&ndash;2015)</p>

Abstract: Purpose To describe trends from 2001 to 2015 in incidence and in-hospital outcomes of patients suffering or not suffering from COPD who had undergone lung transplantation (LTx) in Spain. Methods We used the Spanish National Hospital Discharge Database to select all admissions for LTx. Incidence was estimated overall and according to the presence of COPD. Outcomes included infections, complications, length of hospital stay and in-hospital mortality (IHM). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…In our study, we observed a progressive increase in the number of lung transplantations from 2016 to 2019, following the trend observed in previous years [14]. The International Society for Heart and Lung Transplantation has also recently reported that the number of lung transplant recipients with COPD has also increased by era (1992-2000, 2001-2009, and 2010-2018), although the proportion of COPD recipients compared to other transplant diagnoses has decreased over time.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In our study, we observed a progressive increase in the number of lung transplantations from 2016 to 2019, following the trend observed in previous years [14]. The International Society for Heart and Lung Transplantation has also recently reported that the number of lung transplant recipients with COPD has also increased by era (1992-2000, 2001-2009, and 2010-2018), although the proportion of COPD recipients compared to other transplant diagnoses has decreased over time.…”
Section: Discussionsupporting
confidence: 83%
“…Factors independently associated with IHM in COPD patients after lung transplantation in our study were a higher comorbidity and suffering any complication of the lung transplantation. Both factors have been previously described as predictors of IHM, in addition to others such as age [14]. However, Bello et al, in a retrospective, multicenter cohort study that collected data from 272 adults with lung transplantation, also demonstrated an independent association between pulmonary graft disfunction and SOFA (Sequential Organ Failure Assessment) score with early mortality after lung transplant [34].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…1 In comparison to other disease groups, COPD graft recipients may demonstrate lower rates of in-hospital mortality than other groups, as suggested in a recent analysis of national databases in Spain over a 15-year period. 78 This appears to reflect the comparatively more stable candidate condition immediately prior to transplant.…”
Section: Early Postoperative Care and Rehabilitation In Copd Recipientsmentioning
confidence: 99%